The Material Bases of Meaning - Prodi, Giorgio (Tartu Semiotics Library, 2021)
Contemporary semiotics has often gone too far in proposing language as the model to explain every phenomenon of communication. Giorgio Prodi's seminal book, originally published in Italian in 1977, poses the question from the opposite perspective: his 'natural history of meaning' does not depict a biological universe that behaves as if it spoke, but a cultural universe structured even at its highest levels according to the same modes and processes of mutual adaptation and 'reading' that happen at the level of cells. The picture he paints shows us knowledge at its origin, as a process of environmental adaptation and interpretation, in which the discoveries of biology interact with those of semiotics. Within this natural history of language competence, the book emphasises the remote, primitive phase, which takes place below the threshold of the subjective and the social. Proceeding from there it outlines a holistic hypothesis of semiosis at the cultural level: the elementary phases of the recognition of meaning, which become progressively more complex as the phylogenesis progresses, lead all the way to the construction of linguistic systems in the human animal. This is an investigation of the elementary biological processes in order to identify the material logic that is the foundation of the higher processes of meaning-making - prehistory of the sign, biology of semiosis: from the side of nature and from the side of culture. | Giorgio Prodi (1928-1987) was an Italian oncologist and a pioneer of biosemiotics.